Dynamics of 8G12 competitive antibody in "prime-boost" vaccination of Hepatitis E vaccine - Xing Wu; Pan Chen; Huijuan Lin; Yao Su; Xiaotian Hao; Yufeng Cao; Li Li; Fengcai Zhu; Zhenglun Liang (Taylor & Francis Group, 2017)
Hepatitis E virus still poses a great threat to public health worldwide. To date, Hecolin® is the only licensed HEV vaccine in China. Total anti-HEV antibody has been used to reflect vaccine induced immune response in clinical trials for the lack of robust HEV neutralizing antibody detection methods. In this study, we applied a broad neutralizing mouse monoclonal antibody 8G12 to develop a competitive ELSIA assay and quantified 8G12 competitive antibody (8G12-like antibody) in serum samples. The presence of 8G12-like antibody was detected both from participants from HEV vaccine clinical trial and mice immunized with HEV vaccine. Furthermore, 8G12-like antibody was found to have a similar dynamic pattern as anti-HEV antibody during "prime-boost" vaccination, and the proportion of 8G12-like antibody in anti-HEV antibody increased along boost vaccination. Together with previously reported finding that 8G12 could block the most binding of HEV vaccine induced serum antibody to vaccine antigen, we proposed that 8G12-like antibody might be a promising surrogate for vaccine induced HEV neutralizing antibody and had potential to be used as a convenient indicator for HEV vaccine potency evaluation.